2022
DOI: 10.6004/jadpro.2022.13.1.3
|View full text |Cite
|
Sign up to set email alerts
|

General and Unique Communication Skills Challenges for Advanced Practice Providers: A Mixed-Methods Study

Abstract: Aims: Advanced practice providers are a rapidly growing sector of the health-care field. Despite their relatively new place in the medical establishment, these providers are held to high standards of education, practice, and communication skills. However, the communication needs of these practitioners are somewhat different than those of nurses or physicians. These skills are even more necessary in specialized fields where providers frequently are involved in discussions of prognosis, goals of care, and end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…These scenarios may hinder communication with families and, by extension, degrade the relationship between trainees and APPs. 10,11,29 Disagreements around procedure assignment for APPs and trainees have been reported in surgical and critical care settings. 11,19,20 However, in this study, procedure allocation did not correlate significantly with relationship satisfaction.…”
Section: Role Clarity Communication Procedural Allocationmentioning
confidence: 99%
“…These scenarios may hinder communication with families and, by extension, degrade the relationship between trainees and APPs. 10,11,29 Disagreements around procedure assignment for APPs and trainees have been reported in surgical and critical care settings. 11,19,20 However, in this study, procedure allocation did not correlate significantly with relationship satisfaction.…”
Section: Role Clarity Communication Procedural Allocationmentioning
confidence: 99%
“…More than 90% of oncology APPs report confidence in communicating empathically. 13 In oncology or palliative care settings, patients report feeling empowered, at peace, and in control as a result of the support, guidance, and attention given to them by APPs. 21 In a survey of more than 1,200 oncology patients across 27 sites who had received clinical care from an APP, the overall satisfaction score exceeded 90%.…”
Section: An Optimal Workforce For Cancer Clinical Trialsmentioning
confidence: 99%
“…A needs assessment of 248 advanced practice providers (APPs) found that, in addition to focusing on communication with patients, training to improve communication with colleagues would be beneficial to fostering team function and effectiveness. 10 Other studies have also identified the need to improve team communication. 11,12…”
mentioning
confidence: 99%